Edukasi Bahaya Pinjaman Online bagi Mahasiswa: Strategi Pencegahan dan Solusi Alternatif - Yulasmana, Yoga; Suryaningsih, Suryaningsih; Asri, Yoana Nurul (Penerbit Widina, Widina Media Utama, 2025)
This program aims to provide education on the dangers of online lending (pinjol) and preventive strategies to university students, who are part of Generation Z and considered vulnerable to this phenomenon. The activity was carried out through a Community Service Program (PKM) at a private university in West Java, involving around 40 students. The implementation methods included material presentations, ice-breaking sessions, interactive discussions, and the introduction of alternative solutions such as saving, building emergency funds, and avoiding a consumptive lifestyle triggered by social media and superficial trends. In addition, the concept of cooperatives was introduced as a safer and more sustainable financial solution within the campus environment. The results showed high enthusiasm and active participation from the students in each session, along with increased awareness of the importance of financial literacy. This program is concluded to be an effective initial step in shaping a wiser and financially resilient young generation.ABSTRAKProgram ini bertujuan untuk memberikan edukasi mengenai bahaya pinjaman online (pinjol) serta strategi pencegahan kepada mahasiswa sebagai bagian dari generasi Z yang rentan terhadap fenomena ini. Kegiatan dilakukan melalui Pengabdian kepada Masyarakat (PKM) di salah satu universitas swasta di Jawa Barat, dengan melibatkan sekitar 40 mahasiswa. Metode pelaksanaan mencakup sesi pemaparan materi, ice breaking, diskusi interaktif, serta pengenalan solusi alternatif seperti menabung, membentuk dana darurat, dan menghindari gaya hidup konsumtif. Selain itu, diperkenalkan pula konsep koperasi sebagai solusi keuangan yang aman dan berkelanjutan di lingkungan kampus. Hasil menunjukkan bahwa peserta menunjukkan antusiasme tinggi dan keterlibatan aktif dalam setiap sesi, serta meningkatnya kesadaran akan pentingnya literasi keuangan. Kegiatan ini disimpulkan sebagai langkah awal yang efektif dalam membentuk generasi muda yang lebih bijak dan tangguh secara finansial.